An evaluation of laparoscopic hysterectomy alone versus in combination with laparoscopic myomectomy for patients with uterine fibroids. (March 2017) - Taniguchi, Fumiaki; Koike, Natsuki; Kikukawa, Tadayuki; Yabuta, Maki; Yamaguchi, Masami; Adachi, Emi; Nakayama, Takeo
Abstract: Objective: The purpose of this study was to compare surgical outcomes following conventional laparoscopic hysterectomy (LH) (C-LH) versus the combination method of LH plus laparoscopic myomectomy (LM) (LH + LM) for the treatment of large uterine fibroids. Study design: This study was performed in 56 patients (uterine weights ≥500 g) who underwent either C-LH or LH + LM performed by the same surgeon between May 2010 and May 2016. LH + LM was performed when C-LH was problematic because of poor visibility and/or mobility due to uterine fibroids. Results: The C-LH and LH + LM groups consisted of 27 (48%) and 29 (52%) patients, respectively. The clinical characteristics of patients differed significantly only in the median sizes of the dominant fibroid. The sizes of the dominant fibroid in the C-LH and LH + LM groups were 9.5 cm and 10.7 cm (P = 0.04), respectively. Regarding the surgical outcomes for the C-LH and LH + LM groups, the median uterine weights were 558 g and 737 g (P = 0.03), respectively, the median operating times were 156 min and 173 min (P = 0.23), respectively, and the median intraoperative blood losses were 150 g and 300 g (P = 0.0004), respectively. In all patients, LH was performed without conversion to laparotomy and there were no cases of bladder, ureteral, or gastrointestinal tract injury. There were no postoperative complications of Clavien-Dindo scale ≥ III in either group. Conclusions: When C-LH cannot be performed because of large uterine fibroids that cause poor visibility and/or mobility, LH + LM may allow the procedure to be successfully completed without conversion to laparotomy. However, the latter approach increases the risk for intraoperative blood loss.